A revolution in solar-powered Irrigation: Solar Power as Remunerative Crop (SPaRC) model is being scaled out nationwide in India (WLE-IWMI) - CGIAR Research Program on Water, Land and Ecosystems (2018)
A cooperative business model developed by the CGIAR Research Program on Water, Land and Ecosystems (WLE) and partners is now formally confirmed as one of four components of a total USD 16.4 billion Indian Government farm energy program (KUSUM). Gujarat state has begun scaling out the concept; six other states have begun piloting it under KUSUM. In the model, cooperatives manage a small solar-powered grid for irrigation pumps that sell surplus power to the electric utility.